2021
DOI: 10.3390/ijerph18084361
|View full text |Cite
|
Sign up to set email alerts
|

SARS/MERS/SARS-CoV-2 Outbreaks and Burnout Syndrome among Healthcare Workers. An Umbrella Systematic Review

Abstract: The coronavirus-19 (COVID-19) pandemic is putting a severe strain on all healthcare systems. Several occupational risk factors are challenging healthcare workers (HCWs) who are at high risk of mental health outcomes, including Burnout Syndrome (BOS). BOS is a psychological syndrome characterized by emotional exhaustion, depersonalization, and low personal accomplishment. An umbrella review of systematic reviews and meta-analyses concerning BOS and coronavirus (SARS/MERS/SARS-CoV-2) outbreaks was carried out on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
126
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 69 publications
10
126
0
3
Order By: Relevance
“…The effects found in our cohort correspond to those reported by other researchers: insomnia [33], anxiety [6], burnout [34], reduced happiness [35], lack of job satisfaction and turnover intention [36] are common in HCWs. Many of these outcomes remained constant in our cohort between the first and second wave and it is not easy to understand whether they were a result of the pandemic or were already present in the population.…”
Section: Discussionsupporting
confidence: 90%
“…The effects found in our cohort correspond to those reported by other researchers: insomnia [33], anxiety [6], burnout [34], reduced happiness [35], lack of job satisfaction and turnover intention [36] are common in HCWs. Many of these outcomes remained constant in our cohort between the first and second wave and it is not easy to understand whether they were a result of the pandemic or were already present in the population.…”
Section: Discussionsupporting
confidence: 90%
“…The study indicated that overburdening of HCWs during an extended period of time had increased the symptoms of burnout [ 15 ]. Burnout, however, is a morbid condition that occurs after exposure to chronic stress and is therefore not the first indicator of mental health that can be altered by an epidemic [ 16 ]. There are conflicting findings on the epidemiology of burnout among HCWs working in COVID-19 wards: some studies have found a reduction in burnout rates, for example in US neurosurgeons [ 17 ], in French geriatric facilities [ 18 ], and in Chinese frontline nurses, compared with ordinary ward workers [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first concerns the contagion risk perception, along with safe behaviours among workers external to the healthcare sector during the COVID-19 pandemic. Since February 2020, several scholars have, in fact, analysed the issue of perceived safety, fear of contagion, and the use of PPE only among medical and nursing staff [ 17 , 18 , 19 , 20 , 21 ]. The second gap, regardless of the pandemic period, concerns the fact that the literature on organisational safety largely focuses on the bio-risk hazard from a technical point of view.…”
Section: Introductionmentioning
confidence: 99%